Mental health problems among Jordan University Students - Al- Ziadat, Mariam Awwad (Dirasat: Educational Sciences, 2023)
Objectives: The current study aimed to survey the mental health problems among University of Jordan students and if they differ according to some demographic variables. Methods: The study sample consisted of 501 students, (156) male and (345) female at the undergraduate and postgraduate levels during the academic year of 2021/2022. Stratified random sampling was used to study the student subjects. General Health Questionnaire was used and modified to suit the Jordanian context to measure mental health problems. The validity and reliability of the questionnaire were verified. To answer the study questions, means, standard deviations, and multiple analyses of variance were calculated. Results: The study found moderate levels of mental health issues, with social dysfunction ranking highest, followed by anxiety/insomnia and physical symptoms. Severe depression was low among participants. Statistically significant gender differences (α = 0.05) favored females in total score and all dimensions except social dysfunction, which favored males. Additionally, students in the fifth year and above showed significant advantages in total score and all dimensions, except for social dysfunction, based on academic year. No significant differences were found based on college type or academic stage. Conclusions: The study recommends providing psychological services that take into account students' mental health problems on university campuses and paying attention to providing preventive and counseling services, especially for females and students of the fifth year and above.